1991
DOI: 10.1126/science.1848369
|View full text |Cite
|
Sign up to set email alerts
|

An in Vivo Model of Somatic Cell Gene Therapy for Human Severe Combined Immunodeficiency

Abstract: Deficiency of adenosine deaminase (ADA) results in severe combined immunodeficiency (SCID), a candidate genetic disorder for somatic cell gene therapy. Peripheral blood lymphocytes from patients affected by ADA- SCID were transduced with a retroviral vector for human ADA and injected into immunodeficient mice. Long-term survival of vector-transduced human cells was demonstrated in recipient animals. Expression of vector-derived ADA restored immune functions, as indicated by the presence in reconstituted animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(52 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…Southern blot analysis showed multiplicity of random proviral integration in single epidermal stem cells, as previously shown for human myogenic cells (31,37). The rate of secretion of the exogenous protein by cultures generated by single clones was proportional to the number of integrations per progenitor cell.…”
Section: Resultssupporting
confidence: 72%
“…Southern blot analysis showed multiplicity of random proviral integration in single epidermal stem cells, as previously shown for human myogenic cells (31,37). The rate of secretion of the exogenous protein by cultures generated by single clones was proportional to the number of integrations per progenitor cell.…”
Section: Resultssupporting
confidence: 72%
“…ADA levels are normally highest in thymic T lymphocytes, and it has been postulated that absence of ADA has its most critical impact at the production stage of T lymphopoiesis 13,15 . However, a study by Ferrari et al 16 demonstrated that ADA genecorrected peripheral blood T lymphocytes had prolonged survival after injection into SCIDmice, compared with non-corrected, ADA-deficient T lymphocytes. Thus, ADA expression may also be essential for the survival of mature peripheral blood T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…G ene therapy represents a potentially novel approach to cancer treatment, in which the transfer of genetic material into a specific cell type alters the phenotype of the target cells [1][2][3] in a way that improves the outcome of therapy. Adenoviral vectors have become the most widely used vector for the delivery of prodrug activation transcription units in the field of cancer gene therapy.…”
mentioning
confidence: 99%